(3JbQjQGJ GdTjN YHO GdZfj GdNQGSGfjs - (3YHO GdZfj GdNQGSGfjs
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdbGOQ GdeJYGd (B... (3hHYO deG SGYOfj GdJhajb HJMUjd egeGJ Yde GdCUhd afTQY EPG aj eHGOjg GddZhjIs
(3BNQgG (B:s
(3BNQgG(B: (3aj Pdc GdeHMK hEeG jchf Pdc Yehe eWdb CjVG dcf eY JbGjQ (B... (3ceG CTGQg HYV GdCUhdjf ceG dG jNai (B. (3HMK aj Gdeaghe hGdefWhbs
(3jSHbgG ELGRI ef egOj Hf Ydj Edi GdeDda YHO GdZfj GdNQGSGfjs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3CUhd Gdabgs